Commerce in Banks to Risks Based on the Audit Advantages and Development Prospects (American Journal of Public Diplomacy and International Studies (2993-2157), 2024)
In this article commerce in banks to risks based on audit (Risk-Based Auditing - RBA) advantages and development prospects analysis will be done. To risks based audit of banks main risks identify them manage through financial stability to provide directed. The RBA method in the article traditional to the audit relatively efficiency, commerce banks for importance and in his banking activities risks in minimization place will be lit. That's it additional, international experience based on of the RBA main directions and his modern technologies using development prospects discussion will be done. From this except, in the article this audit method local in banks efficient app reach for recommendations given, including risks fast assessment, digital from platforms use and of the bank internal control system improvement like directions recommendation will be done. Article results commerce in banks to risks based on the audit in development scientific and practical manual being service to do can.